Geographical accessibility to healthcare and malnutrition in Rwanda. (April 2015) - Aoun, Nael; Matsuda, Hirotaka; Sekiyama, Makiko
Abstract: The prevalence of stunting in children less than five years of age is elevated in Rwanda. It is one of the main health challenges upon which the government is struggling to achieve progress. Health centers and district hospitals in Rwanda are expected to provide a package of health services including nutrition related activities, nutritional rehabilitation, education, and growth monitoring. They can hence play a potent role in alleviating malnutrition and stunting in Rwanda. This study tested whether travel time from household clusters to the nearest health center was significantly and negatively associated with the distribution of height-for-age z-scores of younger than five year old children in the eastern province of Rwanda. Data for 974 children was extracted from the Rwanda Demographic and Health Survey (DHS) database. However, since DHS does not contain any information on travel time to health centers, the latter was simulated using AccessMod 4.0, an extension to ArcGIS 9.3.1 that simulates health facilities' catchment areas and travel times to health facilities. Travel time was found to be negatively associated with height-for-age z-scores at the 5% level in a stepwise regression analysis that controlled for wealth index, mother's primary and secondary education, sex of the child, preceding birth interval, and birth order of the child. Field measurements are needed to validate travel time. If validated, results point to the importance of improved access to healthcare facilities as a potential pathway in reducing stunting in Rwanda. Highlights: We simulate travel times from households to health centers in eastern Rwanda. We investigate the association between travel time and height-for-age z-scores. Travel time is negatively associated with height-for-age z-scores. We conclude that increasing access by investing in infrastructure is expensive. We conclude that community based solutions are better for child health.